Research of waveguide accelerating structures with dielectrics - Brizgalov, G.A.; Papkovich, V.G.; Khizhnyak, N.A. (Вопросы атомной науки и техники, 1999)
At a choice of slow-wave structure for application in accelerating technique the main attention is given first of all to its two characteristics: 1) opportunity of use of a partial type of structures in the wider range of energies and 2) the transformation efficiency of high-frequency energy, put to structure, into a kinetic energy of accelerated particles, that eventually leads to comparison of structures on shunt impedance. From this point of view, the waveguides loaded by dielectric disks have doubtless advantages before other traditionally used structures